PENGARUH PEMBELAJARAN KOOPERATIF JIGSAW TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA DI SEKOLAH DASAR - Andriono, Firman Dwi; Marli, Suhardi; Margiyati, KY (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of Jigsaw type cooperative learning on the learning outcomes of fifth grade students of Elementary School 26 of Southeast Pontianak. The method used is the experimental method. This study, using the Quasi Experimental design with the form of Nonequivalent Control Group Design. The research sample in this study were all class V students. Data collection techniques were measurement techniques. The data collection tool used is a test. Based on data analysis, the average post-test results of the experimental class are 70.70 and the post-test control class is 66,10, tcount 1,7168 and ttable 1,6723, because tcount > ttable, then Ha is accepted. So, it can be concluded that there is the influence of Jigsaw type cooperative learning on student learning outcomes. Calculation of effect size obtained by ES = 0,45 which is classified as moderate, which is 0,2<ES<0,8. It can be said that Jigsaw type cooperative learning has a moderate influence on social studies learning outcomes in class V of Elementary School 26 of Southeast Pontianak. Keywords: Influence, Jigsaw, Learning Outcomes Of Students, Social Sciences